Morphological analysis of the vestibular system of guinea pigs poisoned by organophosphate - Cogo,Lícia Assunção (2016)
ABSTRACT INTRODUCTION: The vestibular system is responsible for body balance. There are substances that damage it, causing dizziness; these are termed vestibulotoxic substances. Agrochemicals have been investigated for ototoxicity because of studies that identified dizziness as a recurrent symptom among rural workers' complaints. OBJECTIVE: To histopathologically evaluate the vestibular system in guinea pigs exposed to an organophosphate, and to identify the drug's effects on this system. METHODS: Experimental clinical study. Eighteen guinea pigs were used; six of them poisoned with the organophosphate chlorpyrifos at doses of 0.5 mg/kg/day and seven of them at 1 mg/kg/day; and a control group of five guinea pigs was exposed to distilled water, all for 10 consecutive days. Later, ciliary tufts of saccule and utricle maculae were counted by scanning electron microscopy. RESULTS: Comparing the groups, a one-way ANOVA test for the variable "saccule" ( p = 0.0569) and a Kruskal-Wallis test for the variable "utricle" ( p = 0.8958) were performed, revealing no difference among groups in both variables. CONCLUSION: The histopathologic analysis of the vestibular system of guinea pigs exposed to an organophosphate showed no difference in the amount of ciliary tufts of saccule and utricle maculae at the doses tested, although the result for the variable "saccule" was considered borderline, showing a trend for significance.